2014
DOI: 10.1016/j.meegid.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome analysis and molecular epidemiology of the reemerging porcine epidemic diarrhea virus strains isolated in Korea

Abstract: Porcine epidemic diarrhea virus (PEDV), a member of the Coronaviridae family, is an enveloped, positive-sense, single-stranded RNA virus, which causes severe diarrhea and dehydration in suckling pigs. We detected three PEDV strains from ten small intestine samples from piglets with acute diarrhea and we determined the complete genome sequences of the reemerging Korean PEDV field isolates, except for the noncoding regions from both ends. The complete genome sequences of the strains were identical or almost iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 13 publications
1
17
0
1
Order By: Relevance
“…The five US strains were reported to belong to North American clades I and II, following the PEDV outbreak in April 2013 (Vlasova et al., ). The three Korean strains are thought to be co‐circulating in Korea and showed high homology with the five US strains (Choi et al., ; Lee et al., ). The 31 isolated strains occupied all the 13 cities, suggesting that G3 was the most prevalent genotype in Shandong Province (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The five US strains were reported to belong to North American clades I and II, following the PEDV outbreak in April 2013 (Vlasova et al., ). The three Korean strains are thought to be co‐circulating in Korea and showed high homology with the five US strains (Choi et al., ; Lee et al., ). The 31 isolated strains occupied all the 13 cities, suggesting that G3 was the most prevalent genotype in Shandong Province (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the virulence of highly virulent PEDV was characterized by disease/infection induced by a low infectious dose, short incubation times, severe clinical signs and intestinal lesions, and extensive PEDV replication throughout the intestine (Table 4). In addition to antigenic variation, these disease characteristics also explained why current highly virulent PED outbreaks were so devastating in the major pig producing countries in Asia (Choi et al, 2014;Oka et al, 2014;Sun et al, 2012) and North America (Stevenson et al, 2013;Vlasova et al, 2014). 4.3.…”
Section: Emerging Non-s Indel Pedv Strains Are Highly Virulent In Pigsmentioning
confidence: 99%
“…In 2014, several reports from Asian countries, including Korea, Taiwan and Japan [37,38], suggested that there has been an emergence of US-like PEDV in Asian countries. The results of our study, however, demonstrate that at present, PEDV in Vietnam is not influenced by US-like PEDV strains.…”
Section: Discussionmentioning
confidence: 99%